Bath Electrospinning of Continuous and Scalable Multifunctional MXene‐Infiltrated Nanoyarns. Issue 26 (5th June 2020) - Levitt, Ariana; Seyedin, Shayan; Zhang, Jizhen; Wang, Xuehang; Razal, Joselito M.; Dion, Genevieve; Gogotsi, Yury
Abstract: Electroactive yarns that are stretchable are desired for many electronic textile applications, including energy storage, soft robotics, and sensing. However, using current methods to produce these yarns, achieving high loadings of electroactive materials and simultaneously demonstrating stretchability is a critical challenge. Here, a one‐step bath electrospinning technique is developed to effectively capture Ti3 C2 T x MXene flakes throughout continuous nylon and polyurethane (PU) nanofiber yarns (nanoyarns). With up to ≈90 wt% MXene loading, the resulting MXene/nylon nanoyarns demonstrate high electrical conductivity (up to 1195 S cm −1 ). By varying the flake size and MXene concentration, nanoyarns achieve stretchability of up to 43% (MXene/nylon) and 263% (MXene/PU). MXene/nylon nanoyarn electrodes offer high specific capacitance in saturated LiClO4 electrolyte (440 F cm −3 at 5 mV s −1 ), with a wide voltage window of 1.25 V and high rate capability (72% between 5 and 500 mV s −1 ). As strain sensors, MXene/PU yarns demonstrate a wide sensing range (60% under cyclic stretching), high sensitivity (gauge factor of ≈17 in the range of 20–50% strain), and low drift. Utilizing the stretchability of polymer nanofibers and the electrical and electrochemical properties of MXene, MXene‐based nanoyarns demonstrate potential in a wide range of applications, including stretchable electronics and body movement monitoring. Abstract : Continuous and electroactive MXene‐based nanofiber yarns (nanoyarns) are fabricated using a bath electrospinning method, which captures MXene flakes throughout the entire cross‐section of a nanoyarn, maximizing interactions between nanofibers and flakes. The high stretchability of polymeric nanofibers and the electrical and electrochemical properties of MXene offer a platform for storing energy and sensing body movements in wearable textiles.